Justification of the parameters of vomer section of a seed drill with seed packing - L. F. Babitsky; V. Yu. Moskalevich; A. V. Belov (Аграрная наука Евро-Северо-Востока, 2017)
In the territory of the Republic of Crimea, the production of growing cereal crops in arid conditions is becoming topical. The most effective method is the introduction of a system of saving farming. Existing analogues of seeders with disc coulters in conditions of heavy and loamy soils of the arid region of the Republic of Crimea have limited opportunities. A scheme of sowing with rolling out at the level of seed occurrence and a construction of a vomer section with a roller pressing in the seeds is proposed. This scheme includes: cropping of soil; Seedbed formation; Distribution and indentation of seeds into the soil; Transportation and separation of the undercut loose soil layer; Upsetting and leveling of the soil covering the seed. The structure of the proposed vomer section includes a stand on which a seed conduit, a diffuser and a cultivator leg with two flat-cutting knives and a chisel are fixed. A rolling device with a cutter in the form of an ellipsoid of rotation is hinged to the stand. Behind the packing roller to the frame there are attached lamellar tines, made in the form of segments of a logarithmic spiral. At justifying the design parameters and operating modes, methods of theoretical and agricultural mechanics, mechanics of continuum, elasticity theory, integral and differential calculus were applied. Taking into account the need to ensure an even distribution of the sealing action of the paw on the soil, an analytical expression describing the law of distribution of the contact pressure of the cutting edge of the paw on the soil was obtained, which allowed to justify the shape of the cutting edge of the blade of the paw of the vomer section. The shape of the cutting blade is determined taking into account the physico-mechanical properties of the soil: the deformation index, the shear modulus and the friction coefficient of the blade on the soil. The shape of the compacting roller is determined, which ensures the uniformity of indenting seeds into the soil compacted by the blade. The roller must have the form of a truncated ellipsoid of revolution. Covering the dented seeds with a roller is carried out by the guide trays. Overtake is carried out with the final precoating and leveling of the soil surface.